Investigating the Water Demand and Supply Situation in Baljurashi Governorate, Saudi Arabia - Mohamed, Gamal Khalid Awadelkarim; Ali, Osman Mohamed Najjar; Al-Baggar, Ali Khalaf Ahmed; Hilmi, Hasan Saad Mohammed (Journal of engineering sciences and information technology, 2024)
This study examines the water demand and supply situation in the Baljurashi Governorate of Saudi Arabia during 2018, along with the anticipated changes in these dynamics as a result of upcoming project scenarios from 2018 to 2030. The Water Evaluation and Planning Tool (WEAP) model was utilized to analyze both current and projected domestic water distribution in the region through 2030. Initially, an assessment of current water demand and supply for household use was conducted. Relevant data were collected from a local branch of the Ministry of Environment, Water, and Agriculture (MEWA) in Baljurashi Governorate. This data was input into the WEAP model, which then produced projections for water demand, supplied resources, and unmet needs based on the reference scenario pertaining to the current accounting year. The findings revealed no unmet water demand, according to the model results. To enhance future water availability, the expansion of the Um-ghaith reservoir as a new water source is to be taken into consideration.
Keywords: Baljurashi Governorate; KSA; Water supply; Water Demand; Water Evaluation and Planning; WEAP Software